Difference between the blood samples of patients with bone and joint tuberculosis and patients with tuberculosis studied using machine learning - Ye, Zhen; Zhu, Jichong; Liu, Chong; Lu, Qing; Wu, Shaofeng; Zhou, Chenxing; Liang, Tuo; Jiang, Jie; Li, Hao; Chen, Tianyou; Chen, Jiarui; Deng, Guobing; et al. (Frontiers in Surgery, 2023)
Background: Tuberculosis (TB) is a chronic infectious disease. Bone and joint TB is a common type of extrapulmonary TB and often occurs secondary to TB infection. In this study, we aimed to find the difference in the blood examination results of patients with bone and joint TB and patients with TB by using machine learning (ML) and establish a diagnostic model to help clinicians better diagnose the disease and allow patients to receive timely treatment. Methods: A total of 1667 patients were enrolled in the study. Patients were randomly assigned to the training and validation cohorts. The training cohort included 1268 patients: 158 patients with bone and joint TB and 1110 patients with TB. The validation cohort included 399 patients: 48 patients with bone and joint TB and 351 patients with TB. We used three ML methods, namely logistic regression, LASSO regression, and random forest, to screen the differential variables, obtained the most representative variables by intersection to construct the prediction model, and verified the performance of the proposed prediction model in the validation group. Results: The results revealed a great difference in the blood examination results of patients with bone and joint TB and those with TB. Infectious markers such as hs-CRP, ESR, WBC, and NEUT were increased in patients with bone and joint TB. Patients with bone and joint TB were found to have higher liver function burden and poorer nutritional status. The factors screened using ML were PDW, LYM, AST/ALT, BUN, and Na, and the nomogram diagnostic model was constructed using these five factors. In the training cohort, the area under the curve (AUC) value of the model was 0.71182, and the C value was 0.712. The AUC value of the model was 0.6435779, and the C value was 0.644. Conclusion: We used ML methods to screen out the blood-specific factors—PDW, LYM, AST/ALT, BUN, and Na—of bone and joint TB and constructed a diagnostic model to help clinicians better diagnose the disease in the future.